The Currents of Sufism in the Environmental Movement: Addressing the Environmental Crisis Through a Sufistic Approach - Azkia Rahmi; Zulfan Taufik (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The development of science and technology today shows two contradictory faces. On the one hand, science and technology provide so much convenience for humans, but on the other hand it also provides so many serious, complex and multidimensional global crises such as the environmental crisis. Therefore, this paper tries to “see” the Sufistic approach as the spiritual (esoteric) dimension of Islam towards nature in order to contribute positively to efforts to overcome the environmental crisis. This research is a library-based research with a qualitative approach. Through library research, it is found that Sufism with its doctrines such as wahdat al-wujud, al-insan al-kamil, amanah-khalifah, as well as its practical guidance through maqamat and ahwal, 'ilm and 'amal, can contribute positively in changing the worldview of modern humans who are anthropocentric into spiritualists. Because with these doctrines, modern humans are invited to rediscover the vision of divinity that they have left behind, and understand that nature is a theophany (tajalli) of God that cannot be separated from God Himself. They are also required to treat nature responsibly, as it is an amanah to them as God's khalifah on earth.